SOME BIOLOGICAL OBSERVATIONS ON A HORNET Vespa tropica var. pulchra (Du Buysson), with special reference to its dependence on Polistes wasps - SHOICHI F SAKAGAMI; KUNI'ICHI FUKUSHIM (BRIN Publishing (Penerbit BRIN), 1957)
-